Description of Housewives' Knowledge and Action on Mosquito Nest Eradication (MNE) in Lewa Paku Village, Lewa Sub District, East Sumba District - Yebi Susanti Hambur; Afrona E. L. Takaeb; Enjelita M Ndoen (Media Kesehatan Masyarakat, 2023)
Dengue Hemorrhagic Fever (DHF) is still a health issue in Lewa Paku Village, Lewa sub District, East Sumba District. Mosquitos Nest Eradication (MNE) behavior carried out by the community has not been optimum. This study aimed to know the decription of the knowledge and action of housewives about MNE in Lewa Paku Village, Lewa District, East Sumba Regency. This research was a qualitative research with a phenomenological approach. Data collection was carried out by in-depth interviews with 8 housewives during April 2021. The results showed that housewives’ knowledge about MNE was just focused on preventing adult mosquitoes by fogging. The benefits of MNE activities focused on prevention of avoiding from adult mosquito bites, repelling mosquitos, and avoiding transmission of DFH impacted by mosquitos. This study also found that informants had misperception on mosquito larvae. They considered that mosquito larvae as water fleas. Therefore, they assumed that mosquito larvae was not a health consideration. The MNE processs was carried out by informants by draining, closing the indoor water storage, using mosquito nets during night and avoiding the habit of hanging clothes the room. In addition, the informants had a habit of not applying abate in the water storage, recycling used goods by burning and not applying mosquito repellent lotion during activities or when resting. This study recommended health workers to provide education regarding mosquito larvae eradication, burrying used goods, using mosquito nets, and applying mosquito repellent in order to decrease the number of DHF cases.